PRE-SERVICE TEACHERS TRAINING FOR EFFICIENT HEALTH PROMOTING SCHOOL ACTIVITIES PERFORMANCE - Halyna Sivkovych; Larysa Slyvka; Iryna Hamerska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
All over the world the health of children and youth is considered to be the most important value. Therefore, one task of teachers' education is to train pre-service primary school and kindergarten teachers in a way that enables them to maintain and strengthen their own and their students' health. The aim of this article is to present the comparative results of a study of pre-service teachers' majoring in "Primary Education" and "Preschool Education" readiness to perform health promotion activities, to disclose ways of higher education optimisation to find new content, methods and forms of improving the quality of pre-service school and preschool teachers' training to conduct health promotion work. Our study employed a mixed research method. We developed a questionnaire that consisted of closed-ended and open-ended questions, combined into several sets. We also carried out an anonymous survey of second and third-year students of the Department of Pedagogy of Primary Education (n=133) and the Department of Preschool Education (n=145) of Vasyl Stefanyk Precarpathian National University. The survey was conducted in March-April of 2019. The conducted research shows that the training of pre-service primary school and preschool teachers at higher educational establishments for health maintenance is effective, but needs some improvement. Regarding the motivational indicator of students' readiness for health-promoting work, almost 65% of the respondents believe, that preserving the health of children and youth is the task of educational institutions. As for the cognitive component, more than one-half of our students demonstrate a sufficient level of the relevant knowledge, but their number depends on the problem and the academic discipline. There is also a slight difference in students' answers concerning effective forms and methods of health promotion activity. The results of the study indicate that improvement is possible under the following conditions: purposeful and systematic implementation of pre-service teachers' health education, thorough refining of the course contents, the purpose and tasks of which are related to the development of healthcare competencies; an increase in academic hours for practical training; creation of high-quality textbooks and teaching aids; expanding the curricula of higher educational institutions through optional subjects aimed at the development of students' competencies for their own and their students' health maintenance, as well as habits of exercising in their free time.